MICROZONATION MAP FOR BANDUNG CITY AREA BY USING SHALLOW CRUSTAL SOURCE SCENARIO. - PHILANTHA TJONG (NIM : 25016044), AUBERTA
Microzonation map is the map which is used to know the hazard of earthquake so it can be known the potential damage. The purpose of this thesis is to create microzonation map of Bandung City area by using shallow crustal source scenario. There are several steps to be taken, such an identifying source of earthquake and seismic parameters, attenuation function, deagreggation function, microtremor array test, seismic hazard analysis, propagation of acceleration from bedrock to surface. Seismic hazard analysis was performed using USGS program, and obtained spectral acceleration map in bedrock for probability exceeded 2%, 10%, for T=0 second, T= 0.2 second, and T= 1 second for 50 years service period. Then do deaggregation to get M and R and searched ground motions to be propagated to the surface. Some data are obtained from microtremor array test, such as depth of bedrock, and shear wave acceleration value. The propagation acceleration was done by using NERA program, and obtained surface acceleration values according to the location of NSPT boring log. The surface acceleration map is made at T= 0 seconds, T = 0.2 second, and T=1 second. The mapping process is helped by ArcGIS program.